Isolation and Molecular Identification of Amylolytic Bacteria from Oryctes rhinoceros L. Larvae Decomposing Empty Palm Oil Fruit Bunches - Uto, Sahriani; Arfah, Rugaiyah; Dali, Seniwati; Baharuddin, Maswati (Molekul, 2023)
Oryctes rhinoceros L. is an organism that helps the decomposition of oil palm empty fruit bunches (OPEFB). In the larvae's intestines, there are symbiotic bacteria that are used in the process of food degradation in the digestive system, one of which is amylolytic bacteria. This study aims to isolate and molecular identify amylolytic bacteria that produce amylase enzymes from horn beetle larvae. The techniques are used to screen and isolate bacteria from horn beetle larvae. Bacterial identification was accomplished by microscopically identifying amylase-producing bacterial isolates, performing biochemical tests on selected bacterial isolates, quantifying amylase enzyme activity, and molecularly identifying 16S rRNA. The results of screening and bacterial isolation obtained five isolates. The largest amylolytic bacterial colony index value was obtained in the EA3 isolate, which was 1.370 mm. Bacterial isolates with the highest activity were found in isolates coded EA1 and EA2, namely 0.049 U/mL and 0.0479 U/mL. According to the findings of 16S rRNA molecular identification, isolates EA1 and EA2 had similarities with the bacteria Ochrobactrum sp. and Pseudomonas mendocina.